Jenis Gram dan Morfologi Koloni Bakteri Air Baku Garam - Ninik Agustina; Eka Nurrahema Ning Asih; Ary Giri Dwi Kartika (Program Studi Ilmu Kelautan, Jurusan Perikanan dan Ilmu Kelautan, Fakultas Pertanian, Universitas Mataram, 2022)
Halophilic bacteria are bacteria that can survive in environments with high salt levels, one of which is in salt ponds. Therefore, it is necessary to research to determine the morphology of halophilic bacteria for further use in the identification of bacterial species. This study aimed to determine the colony morphology and types of gram halophilic bacteria. Isolation of halophilic bacteria was carried out using the scatter method. Bacterial purification was carried out by streak method, then morphology identification and bacterial staining were carried out to determine the cell shape and gram of bacteria. The isolation results obtained 4 isolates from raw water (B.AB.1) and reservoir (B.B.1, B.B.2, and B.B.3). The results of the identification of the colony morphology of each bacterial isolate had different colors, shapes, colony edges, elevations, and surfaces. The results of the gram staining test showed that 2 isolates (B.B.1 and B.B.2) were gram-positive and 2 bacterial isolates (B.AB.1 and B.B.3) were gram-negative. The isolates of B.AB.1, B.B.2 and B.B.3 were in the form of bacilli, while the isolates of B.B1 were in the form of cocci.